Can Japanese quail male aggressions toward a female cagemate predict aggressiveness toward unknown conspecifics? - Pellegrini, Stefanía (2017)
The incidence of aggressive behaviors in mature poultry is a topic of highconcern from an economic and from a welfare point of view. Herein,we evaluated in Japanese quail whether the level of male aggressivenessexpressed toward a female cagemate can predict aggressivenesstoward other unknown conspecifics. At 4 wk of age, birds were housedin 90 male-female pairs in breeding cages. Aggressive and reproductivebehaviors were recorded when birds were 11 to 12 wk of age, in20 min observations along 9 d. Males were classified as either high orlow female peckers according to whether they directed more than 5 orno pecks toward their female cagemate (H-FP and L-FP males, respectively;15 males in each group). At 16 wk of age, social interactionsbetween 1 H-FP and 1 L-FP male were evaluated during 10 min in anovel environment with an audience (behind a wire mesh partition)of 2 unknown female conspecifics. According to the male aggressiveperformance, 13 of the 15 H-FP males were winners of the interactionsand also performed a higher (P < 0.01) number of pecks than L-FPmales at the females through the mesh partition. Findings suggests thatmale homecage aggressive performance toward its female cagematemay have predictive value about their aggressive performance withunknown males and also with other females in an unfamiliar surroundingenvironment. Interestingly, a negative relationship was also foundbetween the number of home cage pecks from male to female and thefemale plumage condition suggesting that male aggressive profile couldalso be identified by evaluating the female plumage condition. Furtherstudies aiming to improve the assessment of female plumage conditionin relation to male aggressiveness are needed to assess whether thisvariable can be used as a diagnostic tool of overall male aggressiveness.